Heat‐mediated enrichment of α‐synuclein from cells and tissue for assessing post‐translational modifications. (25th April 2013) - Miranda, Hugo Vicente; Xiang, Wei; de Oliveira, Rita M.; Simões, Tânia; Pimentel, José; Klucken, Jochen; Penque, Deborah; Outeiro, Tiago F.
Abstract: α‐synuclein (α‐syn) is the major component of Lewy bodies, a pathological hallmark of Parkinson's disease and other synucleinopathies. The characterization of α‐syn post‐translational modifications (PTMs), thought to interfere with its aggregation propensity and cellular signaling, has been limited by the availability of extraction methods of endogenous protein from cells and tissues, and by the availability of antibodies toward α‐syn PTMs. Here, by taking advantage of α‐syn thermostability, we applied a method to achieve high enrichment of soluble α‐syn both from cultured cells and brain tissues followed by proteomics analysis. Using this approach, we obtained 98% α‐syn sequence coverage in a variety of model systems, including a transgenic mouse model of PD, and validated the strategy by identifying previously described PTMs such as phosphorylation and N‐terminal acetylation. Our findings demonstrate that this procedure overcomes existing technical limitations and can be used to facilitate the systematic study of α‐syn PTMs, thereby enabling the clarification of their role under physiological and pathological conditions. Ultimately, this approach may enable the development of novel biomarkers and strategies for therapeutic intervention in synucleinopathies. In this study, we describe a method for enriching alpha‐synuclein (α‐syn) from a variety of biological samples, from cultured cells to brain tissues. Enrichment of α‐syn was achieved by heating samples, further facilitating the identification of specific post‐translational modifications by immunoblot, or mass spectrometry‐based techniques. This approach will contribute to the clarification of the role of α‐syn PTMs in Parkinson's disease. Abstract : In this study, we describe a method for enriching alpha‐synuclein (α‐syn) from a variety of biological samples, from cultured cells to brain tissues. Enrichment of α‐syn was achieved by heating samples, further facilitating the identification of specific post‐translational modifications by immunoblot, or mass spectrometry‐based techniques. This approach will contribute to the clarification of the role of α‐syn PTMs in Parkinson's disease.